An Attempt to Understand the Changes in Direction of International Trade in India: Examining the Impact of New International Trade Policy on Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
With this paper, it's depicted that the Indian economy is actually among the growing economic climate with the new international trade policy. International Trade including export or import (EXIM) as the part that is crucial is actually the backbone of any economy. International trade plays a crucial role in the economy of every individual nation. It allows to fulfil the requirements of the population stimulates the internal improvement of the nation. International trade is actually the exchange of services plus goods between nations. The monetary method of the land is majorly determined by its adaptation and viewpoint of imports and exports from various other places so that the international currency could be magnetized to enhance the entire economic scenario. This particular paper is actually an effort to evaluate the significant changes in the direction of Indian International Trade.